Phase Transitions of Ferromagnetic Potts Models on the Simple Cubic Lattice - 王顺 谢志远 陈靖 Bruce Normand 向涛 (Chinese physics letters, 2014)
We investigate the 2- and 3-state ferromagnetic Ports models on the simple cubic lattice using the tensor renorrealization group method with higher-order singular value decomposition （FIOTRG）. HOTRG works in the thermodynamic limit, where we use the Zq symmetry of the model, combined with a new measure for detecting the transition, to improve the accuracy of the critical point for the 2-state model by two orders of magnitude, obtaining Tc = 4.51152469（1）. The 3-state model is far more complex, and we improve the overall understanding of this case by calculating its thermodynamic quantities with high accuracy. Our results verify that the first-order nature of the phase transition and the HOTRG transition temperature benchmarks the most recent Monte Carlo result.